Catalyst for hydrogen production through methane cracking and preparation method thereof
By using mesoporous silica nanoparticles (MSN) as support, metal/MSN composite catalyst was prepared, which solved the problems of high-temperature energy consumption, poor catalyst stability and diverse carbon morphology in methane cracking hydrogen production technology, and achieved high efficiency , stable and controllable methane cracking reaction improves the economic and competitiveness of the process.
Patent Information
- Application Number
- CN202411681542.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-02-25
AI Technical Summary
Methane cracking hydrogen production technology consumes a lot of energy under high temperature conditions, poor stability of traditional metal catalysts, and diverse carbon by-products and affect economics.
Using a metal/MSN composite catalyst with mesoporous silica nanoparticles (MSN) as the support, a uniformly distributed metal/MSN composite material is formed by preparing a metal precursor solution, heating, drying and calcining.
The number of active sites and dispersion of the catalyst is improved, the conversion rate and catalytic efficiency of methane cracking reaction are significantly improved, the reaction temperature and energy consumption are reduced, the controllable generation of carbon material morphology is achieved, and the economics of the process is enhanced. and market competitiveness.
Smart Images

Figure CN119500141A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of methane cracking hydrogen production, and specifically relates to a catalyst for methane cracking hydrogen production and a preparation method thereof. Background Art
[0002] Methane cracking, as a carbon-free hydrogen production technology, has received widespread attention in recent years. Compared with traditional steam reforming, methane cracking does not produce carbon dioxide and can significantly reduce greenhouse gas emissions. Therefore, it shows great application potential under the pressure of global carbon emission reduction.
[0003] However, the promotion of this technology still faces many challenges. First, the reaction usually needs to be carried out under high temperature conditions of up to 1000°C, which leads to huge energy consumption and affects economic benefits. Secondly, traditional metal catalysts are easily deactivated at high temperatures, and their stability is easily reduced due to sintering and carbon deposition, which restricts their long-term catalytic effect. In addition, the carbon by-products generated have various morphologies, including graphite carbon, carbon nanotubes, and amorphous carbon. Different carbon morphologies not only affect the complexity of subsequent processing, but also reduce the economy of the process and the added value of carbon products.
[0004] Controlling the carbon morphology generated by the reaction is an important way to improve economic benefits. Different catalysts and reaction conditions will significantly affect the morphology and structure of carbon byproducts: for example, on nickel-based catalysts, carbon products tend to form onion carbon because nickel particles act as "seeds" to promote the orderly growth of carbon layers; while iron-based catalysts are more likely to form amorphous carbon because they are easier to sinter at high temperatures, resulting in disordered accumulation of carbon layers. In addition, the reaction temperature, catalyst crystal surface and carrier properties will also affect the carbon morphology. For example, high temperature is conducive to the improvement of the degree of graphitization, while low temperature is more likely to form amorphous carbon. By regulating these parameters, it is not only expected to achieve the directional generation of carbon morphology, but also to increase the added value of byproducts, such as high-purity graphite carbon for electrodes and carbon nanotubes for electronic devices.
[0005] The formation mechanism of carbon fibers and carbon nanotubes with higher added value varies in methane cracking reactions due to catalyst characteristics and reaction conditions, but generally involves the adsorption, diffusion and precipitation process of carbon. When methane passes through metal catalysts such as nickel and iron at high temperature, methane molecules first dissociate at the active sites of the catalyst to generate carbon atoms and hydrogen. The dissociated carbon atoms adsorb and diffuse on the catalyst surface, gradually entering the interior of the catalyst particles or migrating along the particle surface. As carbon gradually accumulates in the catalyst, when the carbon concentration reaches saturation, carbon atoms precipitate from one end of the catalyst surface and begin to grow. If the growth process forms an ordered hexagonal graphitic carbon structure, the carbon atoms will accumulate around the catalyst particles into a tubular shape, thus forming carbon nanotubes, whose diameter and morphology are closely related to the size and crystal plane of the catalyst particles; if the carbon atoms are disorderly accumulated, fibrous carbon materials are usually generated. The catalyst may remain in a fixed position (root growth mode) or move with the generated carbon structure (tip growth mode) during the growth process, which also affects the carbon morphology to a certain extent. By regulating parameters such as the pore size, crystal surface, morphology and reaction temperature of the catalyst, the morphology of the generated carbon can be further controlled so that it can develop into a directional growth of carbon fibers or carbon nanotubes.
[0006] Therefore, the development of an efficient, stable catalyst with the ability to control carbon morphology is of great significance for the industrialization of methane cracking hydrogen production technology. Summary of the invention
[0007] The purpose of the present invention is to provide a method to solve the technical problem.
[0008] The present application provides a method for preparing a catalyst for methane cracking to produce hydrogen, comprising:
[0009] Prepare a metal precursor solution: dissolve metal nitrate in deionized water to form a metal salt solution of a specific concentration;
[0010] Add the MSN carrier to the metal salt solution, heat and stir at 85°C to 95°C to ensure that the metal salt and the MSN carrier are fully in contact to form a uniform slurry;
[0011] The slurry was dried in an oven and then calcined at 530°C to 570°C for 2.5 to 3.5 hours to form a uniformly distributed metal / MSN composite material;
[0012] The calcined metal / MSN composite material is collected to obtain a catalyst.
[0013] In one embodiment of the present application, the specific surface area of the MSN carrier is 400-500 m 2 / g. In one embodiment of the present application, the mesopore diameter of the MSN carrier is 2-10 nm. A higher specific surface area helps to increase the catalytic activity of the catalyst and is more conducive to the regulation of the subsequent product carbon morphology.
[0014] In one embodiment of the present application, the specific concentration is the saturated solution concentration of the metal nitrate. Forming a nearly saturated solution can reduce the drying time.
[0015] In one embodiment of the present application, the loading amount of the MSN carrier is 50%, that is, the mass ratio of the metal oxide generated after calcination and oxidation to the MSN carrier is 1: 1. Optionally, the mass calculation formula of the metal oxide is: (mass of nitrate * molar mass of oxide after oxidation) / molar mass of nitrate; the loading amount calculation formula is: mass of metal oxide formed after calcination / total mass after calcination = 50%.
[0016] In one embodiment of the present application, the metal salt solution is a mixed solution of iron nitrate and aluminum nitrate in a molar ratio of 1: 1. When the catalyst is used in a methane cracking reaction, a high conversion rate can be obtained and a large amount of carbon nanotube material can be generated.
[0017] In one embodiment of the present application, the metal salt solution is a nickel nitrate solution. The catalyst can effectively reduce the minimum temperature of the methane cracking reaction.
[0018] In one embodiment of the present application, the metal salt solution is a mixed solution of iron nitrate and cobalt nitrate in a molar ratio of 1:1, which can further improve the catalytic efficiency of the catalyst.
[0019] Correspondingly, the present application also provides a catalyst for producing hydrogen from methane by cracking, which is prepared by the method for preparing the catalyst for producing hydrogen from methane by cracking as described above.
[0020] The beneficial effects of the present invention are:
[0021] 1. Increase in the number of active sites
[0022] By designing a multi-pore carrier, a larger specific surface area and more pore structures are provided, so that the alloy atom catalyst can be evenly dispersed on the surface and in the pores of the carrier. This greatly increases the number of active sites of the catalyst, thereby improving the overall catalytic efficiency.
[0023] 2. High dispersion of active sites
[0024] The dispersion of the alloy atom catalyst is precisely controlled, making the active sites of the catalyst highly dispersed, avoiding adverse factors such as aggregation and sintering. Such dispersion not only improves the reaction activity of the catalyst, but also extends its service life and reduces the need for frequent catalyst replacement.
[0025] 3. Improvement of reaction activity and conversion rate
[0026] Due to the increase and high dispersion of active sites, the reaction activity of the catalyst is significantly improved, achieving a higher conversion rate in the methane cracking reaction. This not only improves the catalytic performance, but also greatly reduces the temperature and energy consumption required for the reaction, reducing the energy cost in industrial production.
[0027] 4. Controllable generation of carbon material morphology
[0028] By adjusting the composition and proportion of the metal precursor solution, the morphology of the carbon material generated after catalytic cracking can be independently controlled. This directional control not only optimizes the catalytic efficiency during the catalytic process, but also generates carbon-based materials with specific morphologies, such as carbon fibers, carbon nanotubes, graphene, etc.
[0029] 5. Improvement of applicability and economy
[0030] This ability to control the morphology of carbon materials expands the applicability of catalysts in different industrial fields. For example, the generated carbon nanotubes and graphene have important application value in energy storage devices, electronic components and other fields. By generating high value-added carbon materials, the economic benefits of the catalytic process are improved, making it more competitive in the production industry.
[0031] Other features and advantages of the present invention will be described in the following description, and partly become apparent from the description, or understood by practicing the present invention. The purpose and other advantages of the present invention are realized and obtained by the structures particularly pointed out in the description and the drawings.
[0032] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, preferred embodiments are given below and described in detail with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0034] Figure 1 is a schematic diagram comparing the methane conversion rates of Example 1 and Comparative Example 1;
[0035] Figure 2 is a schematic diagram comparing the methane conversion rates of Example 2 and Comparative Example 2;
[0036] Figure 3is a schematic diagram comparing the methane conversion rates of Example 3 and Comparative Example 3;
[0037] Figure 4 This is an electron microscope photo of mesoporous silica;
[0038] Figure 5 This is a TEM photo of the product after the reaction in Example 2;
[0039] Figure 6 This is a TEM photo of the product after the reaction in Example 3;
[0040] Figure 7 This is a TEM-EDS photo of the product after the reaction in Example 2. DETAILED DESCRIPTION
[0041] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the accompanying drawings. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0042] About the synthesis of MSN (mesoporous silica nanoparticles):
[0043] Mesoporous silica nanoparticles (MSNs) can be synthesized by the classic sol-gel method. By controlling the reaction conditions, nanoparticles with specific pore size structure and morphology can be obtained. The following is an example of an optional specific preparation step:
[0044] Preparation of precursor solution: Dissolve hexadecyltrimethylammonium chloride (CTAB) as template, ammonia as catalyst, and ethylene glycol as solvent in deionized water and mix thoroughly under a stirrer. This step ensures the formation of a mesoporous structure by forming uniform template micelles.
[0045] Addition of silicon source: Stir the above solution for 30 minutes at 50°C to ensure full dissolution and uniform distribution of the template. Then slowly add tetraethyl silicate (TEOS) as a silicon source, and add 3-(triethoxysilylpropyl)amine to further enhance the formation of the silicon-oxygen network. This stage will trigger the hydrolysis and polycondensation reaction of silicate, forming a stable silicon-oxygen skeleton structure and converting the solution into a white suspension. Add 25.2g of urea and stir for 3h.
[0046] Reaction process: The suspension was heated to 80°C and stirred for 2 hours to ensure further growth and solidification of the particles. After the reaction, the solution was placed in a refrigerator to cool and stratify, which was conducive to the separation of particle precipitation.
[0047] Particle collection and washing: The white precipitate generated by the reaction is collected by centrifugation or filtration. The precipitate is washed several times with a mixture of distilled water and ethanol to remove residual reactants and templates.
[0048] Drying and calcination: The obtained MSNs were finally dried at 110 °C overnight to remove the residual solvent, and then calcined at 550 °C for 3 hours to remove the CTAB template, and finally silica nanoparticles with regular mesoporous structure were obtained.
[0049] Pore size and specific surface area screening: The specific surface area range is preferably 400-500m 2 / g of silica nanoparticles with a mesopore size range of 2 to 10 nm are used for the next step of catalyst synthesis. The higher specific surface area helps to increase the catalytic activity of the catalyst and is more conducive to the regulation of the subsequent product carbon morphology.
[0050] Figure 4 The electron microscope photos of the prepared mesoporous silica, where (a) is stirred for 30 minutes, and (b) is stirred for 3 hours. The minimum particle size is about 500nm, and the maximum particle size is about 3μm.
[0051] The method for preparing the catalyst for methane cracking to produce hydrogen in the embodiment comprises the following steps:
[0052] Prepare a metal precursor solution: dissolve metal nitrate in deionized water to form a metal salt solution of a specific concentration;
[0053] Add the MSN carrier to the metal salt solution, heat and stir at 85°C to 95°C to ensure that the metal salt and the MSN carrier are fully in contact to form a uniform slurry;
[0054] The slurry was dried in an oven and then calcined at 530°C to 570°C for 2.5 to 3.5 hours to form a uniformly distributed metal / MSN composite material;
[0055] The calcined metal / MSN composite material is collected to obtain a catalyst.
[0056] The following is an example of specific preparation:
[0057] Example 1: Preparation of nickel-supported porous catalyst
[0058] Weigh 5.81g nickel nitrate hexahydrate and dissolve it in 100mL deionized water, take 1.20g MSN and add it to the metal salt solution, heat it at 90°C and stir it with a magnetic stirrer until a uniform slurry is formed. The resulting slurry is dried in an oven overnight, then calcined at 550°C for 3 hours, taken out and ground into powder with a mortar for use.
[0059] 0.2 g of nickel-loaded porous carrier catalyst powder was added to a tubular furnace, and methane gas was introduced at a flow rate of 20 mL / min. The reaction temperature was 800° C. and a gas chromatograph was connected to conduct a catalytic activity test.
[0060] Catalytic activity: The timing started when the reaction temperature reached 800°C. The reaction time was 3 hours. The gas chromatograph data was recorded every 20 minutes. The converted conversion rates were 24.6%, 20.38%, 23.34%, 21.64%, 21.48%, 20.86%, 19.62%, 18.34%, 10.32% and 9.81%, respectively.
[0061] Example 2: Preparation of iron-cobalt loaded porous carrier catalyst
[0062] Weigh 4.04g of ferric nitrate nine hydrate and 2.91g of cobalt nitrate hexahydrate and dissolve them in 100mL of deionized water. Take 1.20g of MSN and add it to the metal salt solution. Heat it at 90°C and stir it with a magnetic stirrer until a uniform slurry is formed. The resulting slurry is dried in an oven overnight, then calcined at 550°C for 3 hours, and then ground into powder with a mortar for use.
[0063] 0.2 g of iron-cobalt loaded porous carrier catalyst powder was added into a tubular furnace, and methane gas was introduced at a flow rate of 20 mL / min. The reaction temperature was 800° C. and a gas chromatograph was connected to conduct a catalytic activity test.
[0064] Catalytic activity: The timing started when the reaction temperature reached 800°C. The reaction time was 3 hours. The gas chromatograph data was recorded every 20 minutes. The converted conversion rates were 38.25%, 42.5%, 43.6%, 38.2%, 35.0%, 30.6%, 28.7%, 25.4%, 21.8% and 18.7%, respectively.
[0065] Dispersion Characterization: TEM-EDS was used to characterize the metal elements in the catalyst to observe the dispersion in the catalyst.
[0066] Example 3: Preparation of Fe-Al-supported porous catalyst
[0067] Weigh 4.04g of ferric nitrate nine hydrate and 3.75g of aluminum nitrate hexahydrate and dissolve them in 100mL of deionized water. Take 1.20g of MSN and add it to the metal salt solution. Heat it at 90°C and stir it with a magnetic stirrer until a uniform slurry is formed. The resulting slurry is dried in an oven overnight, then calcined at 550°C for 3 hours, and then taken out and ground into powder with a mortar for use.
[0068] 0.2 g of iron-aluminum loaded porous carrier catalyst powder was added into a tubular furnace, and methane gas was introduced at a flow rate of 20 mL / min. The reaction temperature was 800° C. and a gas chromatograph was connected to conduct a catalytic activity test.
[0069] Catalytic activity: The timing started when the reaction temperature reached 800°C. The reaction time was 3 hours. The gas chromatograph data was recorded every 20 minutes. The converted conversion rates were 48.8%, 53.8%, 39.9%, 35.3%, 33.0%, 29.9%, 27.5%, 24.8%, 22.6% and 18.2%, respectively.
[0070] Comparative Example 1:
[0071] Conventional commercial silica particles (micrometer size) were used as carriers for the preparation of the catalyst. 5.81 g of nickel nitrate hexahydrate was weighed and dissolved in 100 mL of deionized water. 1.20 g of silica was added to the metal salt solution, heated at 90 ° C and stirred with a magnetic stirrer until a uniform slurry was formed. The resulting slurry was dried in an oven overnight, then calcined at 550 ° C for 3 hours, taken out and ground into powder with a mortar for later use. 0.2 g of catalyst powder was added to a tubular furnace, and methane gas was introduced at a flow rate of 20 mL / min. The reaction temperature was 800 ° C, and a gas chromatograph was connected for catalytic activity testing.
[0072] Catalytic activity: The timing started when the reaction temperature reached 800°C. The reaction time was 3 hours. The gas chromatograph data was recorded every 20 minutes. The converted conversion rates were 17.0%, 16.2%, 13.7%, 12.8%, 12.0%, 11.2%, 11.3%, 11.2%, 10.5% and 10.3%, respectively.
[0073] Comparative Example 2:
[0074] Without using a carrier, weigh 4.04g of ferric nitrate nine hydrate and 2.91g of cobalt nitrate hexahydrate and dissolve them in 100mL of deionized water and stir evenly. Dry in an oven overnight, then calcine at 550℃ for 3 hours, take it out and grind it into powder with a mortar for use. Add 0.2g of catalyst powder to a tubular furnace, pass methane gas at a flow rate of 20mL / min, the reaction temperature is 800℃, and connect to a gas chromatograph for catalytic activity test.
[0075] Catalytic activity: The timing started when the reaction temperature reached 800°C. The reaction time was 3 hours. The gas chromatograph data was recorded every 20 minutes. The converted conversion rates were 20.0%, 14.8%, 12.7%, 11.9%, 9.9%, 8.6%, 7.7%, 7.4%, 6.3% and 5.1%, respectively.
[0076] Comparative Example 3:
[0077] Weigh 4.04g of ferric nitrate nine hydrate and dissolve it in 100mL of deionized water. Do not add aluminum nitrate solution. Take 1.20g of the prepared MSN and add it to the metal salt solution. Heat it at 90°C and stir it with a magnetic stirrer until a uniform slurry is formed. The resulting slurry is dried in an oven overnight, then calcined at 550°C for 3 hours, taken out and ground into powder with a mortar for use. Add 0.2g of catalyst powder to a tubular furnace, pass methane gas at a flow rate of 20mL / min, the reaction temperature is 800°C, and connect the gas chromatograph for catalytic activity test.
[0078] Catalytic activity: The timing started when the reaction temperature reached 800°C. The reaction time was 3 hours. The gas chromatograph data was recorded every 20 minutes. The converted conversion rates were 18.3%, 17.9%, 18.2%, 17.5%, 17.4%, 18.2%, 17.2%, 18.2%, 17.1%, and 17.2%, respectively.
[0079] See also Figure 1 In Example 1, the nickel-supported catalyst with a high specific surface area MSN carrier prepared by the present invention is used, and in Comparative Example 2, the nickel-supported catalyst with a micron-sized commercial SiO2 as a carrier is used. In comparison, the catalyst prepared by the present invention has a more significant advantage in the same methane cracking reaction. It can be seen that in the case of a high specific surface area loading, the active metal component has a better dispersion effect and can better contact with methane to undergo cracking reaction.
[0080] See also Figure 2 , Example 2 used the iron-cobalt alloy supported catalyst prepared by the present invention, and Comparative Example 2 used an unsupported iron-cobalt alloy supported catalyst. In addition to having a higher methane conversion rate, the supported catalyst also has a longer catalyst service life. At the end of the reaction, it still has a conversion rate advantage of about 13% over the unsupported catalyst.
[0081] See also Figure 3 , Example 3 uses the iron-aluminum alloy supported catalyst prepared by the present invention, and Comparative Example 3 uses the single iron supported catalyst prepared by the present invention. The catalyst to which aluminum nitrate solution was added during the preparation process can show a better methane conversion rate than the single iron catalyst. However, after research, it was found that aluminum cannot produce activity for methane cracking reaction (the principle is: catalytic methane cracking reaction usually requires metal catalysts (such as iron, nickel, cobalt, etc.) to adsorb and activate the CH bonds in methane. Aluminum atoms lack the d-orbital electrons of transition metals, so they are relatively weak in catalytic activity and cannot effectively interact with methane molecules), so the addition of aluminum should produce a bimetallic synergistic effect with iron in the catalyst, so that the catalyst can produce higher catalytic activity.
[0082] Figure 5 It can be seen that the carbon products produced by the reaction of the porous carrier catalyst supported by iron and cobalt are mainly graphite carbon (blocky transparent thin layer) wrapped outside the catalyst particles (black dots in the figure), and a small amount of carbon nanotube structure (tubular thin layer in the figure). Figure 6 As shown, the carbon products generated by the iron-aluminum supported catalyst in Example 3 after the reaction mainly present tubular carbon nanotubes and carbon fibers. Figure 5 ), when the cobalt in the catalyst is replaced by aluminum, the morphology of the carbon product generated by the reaction changes from graphite carbon to carbon nanotubes. This result shows that the morphology of the carbon byproduct after the reaction can be effectively controlled by selecting different metal loadings.
[0083] like Figure 7 As shown, EDS characterization shows that the alloy phase in the alloy catalyst prepared by the present invention can be evenly dispersed, making the bimetallic promotion effect more significant, thereby improving the catalytic activity of the catalyst.
[0084] In summary, the innovation of the present invention is:
[0085] 1. Directed production of carbon materials with desired morphology
[0086] The present invention realizes the directional production of carbon material morphology, such as carbon nanotubes, graphene, etc., by rationally adjusting the metal types and proportions of the alloy. This design not only improves the economic benefits of the catalytic process, but also expands the application range of the catalyst and enhances its industrial application value.
[0087] 2. High specific surface area and excellent gas diffusion performance
[0088] The present invention utilizes the high specific surface area and good gas diffusion performance of the porous carrier to achieve efficient cracking of methane at a relatively low temperature. Compared with traditional catalysts, the present invention can significantly increase the conversion rate of methane and improve catalytic performance while reducing the reaction temperature.
[0089] 3. Metal synergy effect in alloys
[0090] By precisely controlling the metal synergistic effect in the alloy, the present invention significantly improves the stability and activity of the catalyst and prolongs the service life of the catalyst. This synergistic effect enables the catalyst to maintain high activity during long-term reactions and reduces the possibility of catalyst deactivation.
[0091] 4. Preparation method
[0092] In the preparation process of the catalyst, mesoporous silica nanoparticles are first used as a carrier, and then the alloy atoms are loaded by impregnation with the required metal salt solution. This preparation method has mild reaction conditions, simple process, good operability, suitable for large-scale production, and meets the requirements of green chemistry.
[0093] Based on the above ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above description. The technical scope of the present invention is not limited to the contents of the specification, and its technical scope must be determined according to the scope of the claims.
Claims
1. A method for preparing a catalyst for methane cracking to produce hydrogen, characterized in that: include: Prepare a metal precursor solution: dissolve metal nitrate in deionized water to form a metal salt solution of a specific concentration; Add the MSN carrier to the metal salt solution, heat and stir at 85°C to 95°C to ensure that the metal salt and the MSN carrier are fully in contact to form a uniform slurry; The slurry was dried in an oven and then calcined at 530°C to 570°C for 2.5 to 3.5 hours to form a uniformly distributed metal / MSN composite material; The calcined metal / MSN composite material is collected to obtain a catalyst.
2. The method for preparing a catalyst for producing hydrogen by cracking methane according to claim 1, characterized in that: The specific surface area of the MSN carrier is 400-500m 2 / g.
3. The method for preparing a catalyst for producing hydrogen by cracking methane according to claim 1, characterized in that: The mesopore diameter of the MSN carrier is 2-10 nm.
4. The method for preparing a catalyst for producing hydrogen by cracking methane according to claim 1, characterized in that: The specific concentration is the saturated solution concentration of the metal nitrate.
5. The method for preparing a catalyst for producing hydrogen by cracking methane according to claim 1, characterized in that: The weight ratio of MSN support to metal oxide after calcination was 1:
1.
6. The method for preparing a catalyst for producing hydrogen by cracking methane according to claim 1, characterized in that: The metal salt solution is a mixed solution of ferric nitrate and aluminum nitrate in a molar ratio of 1:
1.
7. The method for preparing a catalyst for producing hydrogen by cracking methane according to claim 1, characterized in that: The metal salt solution is a nickel nitrate solution.
8. The method for preparing a catalyst for producing hydrogen by cracking methane according to claim 1, characterized in that: The metal salt solution is a mixed solution of ferric nitrate and cobalt nitrate in a molar ratio of 1:
1.
9. A catalyst for producing hydrogen by cracking methane prepared by the method for preparing a catalyst for producing hydrogen by cracking methane according to any one of claims 1 to 8.